2003
DOI: 10.1103/physrevlett.91.097906
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Monitoring of Rabi Oscillations in a Josephson Flux Qubit

Abstract: Under resonant irradiation, a quantum system can undergo coherent (Rabi) oscillations in time. We report evidence for such oscillations in a continuously observed three-Josephson-junction flux qubit, coupled to a high-quality tank circuit tuned to the Rabi frequency. In addition to simplicity, this method of Rabi spectroscopy enabled a long coherence time of about 2.5 micros, corresponding to an effective qubit quality factor approximately 7000.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
133
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(137 citation statements)
references
References 19 publications
4
133
0
Order By: Relevance
“…More recently superconducting qubits were shown to act as artificial two-level atoms, displaying Rabi oscillations, Ramsey fringes, and further quantum effects 1,2,3 . Coupling such qubits to resonators 4,5,6,7 brought the superconducting circuits into the realm of quantum electrodynamics (circuit QED). It opened the perspective to use superconducting qubits as micro-coolers or to create a population inversion in the qubit to induce lasing behavior of the resonator 8,9,10,11 .…”
mentioning
confidence: 99%
“…More recently superconducting qubits were shown to act as artificial two-level atoms, displaying Rabi oscillations, Ramsey fringes, and further quantum effects 1,2,3 . Coupling such qubits to resonators 4,5,6,7 brought the superconducting circuits into the realm of quantum electrodynamics (circuit QED). It opened the perspective to use superconducting qubits as micro-coolers or to create a population inversion in the qubit to induce lasing behavior of the resonator 8,9,10,11 .…”
mentioning
confidence: 99%
“…[12][13][14] With regard to using superconducting systems in quantum technologies, it has been shown that Josephson weak link circuits, and in particular SQUID rings in the quantum regime, are highly nonperturbative in nature and can generate very strong nonlinear interactions with classical circuit environments. [15][16][17][18] In this paper we provided a demonstration that this nonperturbative ͑nonlinear͒ behavior is crucial to the understanding of the interaction of SQUID rings with circuit environments. In this work we first consider the adiabatic ͑ground state͒ interaction of a quantum regime SQUID ring inductively coupled to a classical parallel resonance LC ͑tank͒ circuit.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement record in such a situation is a fluctuating current I(t) that accumulates a distinguishable signal-to-noise ratio after some time. 17,18 On one hand, the weak coupling between detector and qubit(s) permits the quantum system to remain relatively well isolated from "outside" classical noise. On the other hand, it means that instead of simple abrupt collapse, 19 we have to deal with a theory of continuous (weak) mea-surements of a single quantum system.…”
Section: Introductionmentioning
confidence: 99%